THE DEVELOPMENT OF A DIGITAL FLIPBOOK FOR IPAS LEARNING CONTENT BASED ON BALINESE LOCAL WISDOM TO IMPROVE LEARNING OUTCOMES OF FOURTH GRADE ELEMENTARY SCHOOL STUDENTS - Muzakki, Muhammad Fajar; Irwan Febryan; Nyoman Ayu Putri Lestari (Jurnal Ilmiah Pendidikan Citra Bakti, 2026)
This research focuses on creating a digital flipbook based on Balinese local wisdom for the "Indonesiaku Kaya Budaya" science and social studies (IPAS) topic. The goal is to evaluate how valid, practical, and effective this tool is in boosting the academic performance of fourth-grade students. The study applies the Research and Development (R&D) approach, specifically utilizing the ADDIE framework, which includes analysis, design, development, implementation, and evaluation to build the media. Participants in this study were fourth graders from SDN 2 Tegalbadeng Barat. To gather data, the researcher used validation forms from experts, feedback surveys from both teachers and students, as well as pretest and posttest assessments to measure learning progress. Findings revealed that the digital flipbook is highly valid, scoring 91.48% from content experts and 92.14% from media experts. In terms of usability, the media proved to be highly practical, receiving a 95.20% positive response from teachers and 91.20% from students. Furthermore, the tool successfully enhanced student learning. This is proven by a notable increase in the average test scores, which jumped from 36.89 to 78.92, supported by a paired t-test significance of < 0.001. In conclusion, this Balinese local wisdom-based digital flipbook is a valid, practical, and effective educational medium for improving the learning outcomes of fourth-grade students.